Effectiveness of the support program of providing food baskets for needy undernourished pregnant and lactating mothers in Iran: a case study of population level intervention - Sepideh Dolati; Ali Barzegar; Fatemeh Mohammadi-Nasrabadi; Morteza Abdollahi; Rahim Khodayari-Zarnaq (BMC Pregnancy and Childbirth)
Abstract Background Inadequate maternal nutrition has adverse consequences for both mother and fetus. This study was conducted with the aim of investigating the effectiveness of the food basket support program for undernourished pregnant and lactating mothers on maternal and infant weight gain and maternal anemia. Methods The present study was conducted retrospectively and semi-experimentally in 2023. Pregnant women (n = 652) were divided into Three groups: food basket (intervention), eligible non-supported (control), and non-needy control group. If a pregnant mother met one of the following criteria and was in financial need, she entered the program: body mass index (BMI) < 18.5 kg/m2, body weight < 45 kg, hemoglobin < 11 g/dL, multiple birth, unfavorable weight gain (WG) during pregnancy. The collected information includes the mothers’ socio-economic characteristics, BMI, WG and hemoglobin in the fourth and eighth months of pregnancy, the weight and head circumference of the infants at the time of birth, and the trend of the infants’ weight and type of nutrition at 2, 4 and 6 months. Repeated measurement ANOVA was used to compare data in several times. Results There was a significant difference between the three groups in terms of educational and occupational level. The prevalence of anemia was remained unchanged in the food basket group (from 23 to 25%); however, it increased in the eligible non-supported group (from 22 to 37%) and non-needy control (from 0.5 to 8.6%) groups. The difference in mother’s WG in the fourth and eighth months of pregnancy was evident between the intervention group and others. The birth weight of infants in the eligible non-supported group (3036.6 ± 457.6) was significantly lower than the non-needy control group (3161.0 ± 440.4). Repeated measurement ANOVA showed the time*group interaction was significant in weight of infants in 2, 4, and 6 months that means groups were significantly different in terms of infant weight during 6 months of age (p < 0.05). Conclusion The present study showed that participation in the food basket support program could lead to an increase in the appropriate weight of mothers, an improvement in birth weight and an increase in the weight of infants compared to the non-needy control group.